Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M95 - Betzler, Christian; Eberli, Gregor P; Lindhorst, Sebastian; Ludwig, Juliane; Schutter, Ilona; Ulferts, Leonie; Wunsch, Marco (PANGAEA, 2022)
Multibeam bathymetry raw data using the ship's own Kongsberg EM 122 multibeam echosounder was mostly continuously recorded during RV METEOR cruise M95. Data was recorded on 19 days between 2013-04-01 and 2013-04-20. This dataset contains a survey about 120 km west of the coast of the Bahamas. The approximate average depth of the entire dataset is around 600m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) files from the cruise are not archived at the BSH, thus no SVP files are added to this dataset. However, data analysis of the multibeam raw data revealed that SVP has been changed several times during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area "Data management and Digitalization" (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. It appears, that the Kongsberg EM 710 multibeam echosounder was simultaneously running during data acquisition since the coverage is nearly the same (https://doi.org/10.1594/PANGAEA.942462). However this did not significantly affecting data quality (nevertheless, based on the data, whether a direct interference between both system exists is unknown). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).
Keywords: Bathymetry; Multibeam Echosounder